Fluorescent phosphorus dendrimers excited by two photons: synthesis, two-photon absorption properties and biological uses - Caminade, Anne-Marie; Zibarov, Artem; Cueto Diaz, Eduardo; Hameau, Aurélien; Klausen, Maxime; Moineau-Chane Ching, Kathleen; Majoral, Jean-Pierre; Verlhac, Jean-Baptiste; Mongin, Olivier; Blanchard-Desce, Mireille (Beilstein Journal of Organic Chemistry, 2019)
Different types of two-photon absorbing (TPA) fluorophores have been synthesized and specifically functionalized to be incorporated in the structure of phosphorus dendrimers (highly branched macromolecules). The TPA fluorophores were included in the periphery as terminal functions, in the core, or in the branches of the dendrimer structures, respectively. Also the functionalization in two compartments (core and surface, or branches and surface) was achieved. The consequences of the location of the fluorophores on the fluorescence and TPA properties have been studied. Several of these TPA fluorescent dendrimers have water-solubilizing functions as terminal groups, and fluorophores at the core or in the branches. They have been used as fluorescent tools in biology for different purposes, such as tracers for imaging blood vessels of living animals, for determining the phenotype of cells, for deciphering the mechanism of action of anticancer compounds, and for safer photodynamic therapy.
Keywords: bioimaging; dendrimer; fluorescence; phosphorus; two-photon absorption